INNOVATIVE APPROACH TO THE DEVELOPMENT OF THE CONSTRUCTION INDUSTRY OF KAZAKHSTAN - Adykhanov, Sanzhar; Zhamankulova, Asel (SWorld-Ger Conference proceedings, 2025)
The study is devoted to improving enterprise management using a platform-based approach. This is one of the relevant directions for strengthening the market positioning of construction enterprises in Kazakhstan. The key directions and trends in the digit